Autologous Fibrin Sealant in Tubeless Percutaneous Nephrolithotomy; A Prospective Study - Ziaee, Seyyed Amir Mohsen; sarhangnejad, Reza; Abolghasemi, Hassan; Eshghi, Peyman; Radfar, Mohammad Hadi; Ahanian, Ali; kardoust parizi, mehdi; Amirizadeh, Nasser; nouralizadeh, akbar (Urology Journal, 2013)
Purpose: To evaluate the efficacy of autologous single-donor fibrin glue after tubeless percutaneous nephrolithotomy (PCNL). Materials and Methods: Forty-three patients were planned for tubeless PCNL in a prospective cohort study and randomized in two groups with or without using fibrin glue. Randomization method was based on the computer-generated random numbers. Results: Transfusion, urinary leakage, or major complications were found in neither of the groups. There was no difference between two groups in stone free rate (P = .53), and changes in hemoglobin (P = .61) and serum creatinine (P = .63) level. Conclusion: Although autologous fibrin glue did not play any significant role in improving results or decreasing complications after tubeless PCNL in our study, its use was safe and did not increase complications.